Religiosity And Its Consequences in Halal Food Purchasing Behaviour: An Empirical Evidence from Tarakan, Indonesia and Tawau, Malaysia - Marso; Haslinda Hasan (Universiti Malaysia Sabah, 2019)
Halal is a religious issue and an opportunity to increase sale and acquire a competitive advantage. This study aims to present the structural relationship between religiosity, attitude, and behavioural intention towards purchasing halal products. A total of 299 valid and usable questionnaires were obtained from the respondents in Tarakan (Indonesia) and Tawau (Malaysia). Employing SEM-PLS approach, data was analyzed using SmartPLS Professional 3.0. The findings demonstrated that religiosity directly and significantly influenced attitude; religiosity directly and significantly influenced intention; attitude directly influenced behavioural intention; the mediating role of attitude towards the influence of religiosity on behavioural intention is partially mediated. Theoretically, the findings affected the development of consumer behaviour theory through Value-Attitude-Behaviour (VAB) Hierarchy Model. The results would benefit the industry players and policymakers to improve their marketing strategy and policy decisions of making Indonesia and Malaysia Muslim consumers be more aware and support the halal foods and products.